2020
DOI: 10.1097/aog.0000000000003979
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Disease Severity in Hospitalized Pregnant Women With Coronavirus Disease 2019 (COVID-19)

Abstract: Table 1. Countries, territories or areas with reported laboratory-confirmed COVID-19 cases and deaths. Data as of 13 April 2020 * Reporting Country/ Territory/Area † Total confirmed ‡ cases Total confirmed new cases Total deaths Total new deaths Transmission classification § Days since last reported case Western Pacific Region China 83597 115 3351 2 Clusters of cases Republic of Korea 10537 25 217 3 Clusters of cases Japan 7255 507 102 4 Clusters of cases Australia 6322 33 61 4 Clusters of cases Malaysia 4683 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
151
2
30

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(199 citation statements)
references
References 13 publications
12
151
2
30
Order By: Relevance
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…Notably, subject n. 17 was the only one to deliver prematurely at week 34. Prematurity was indeed reported to be more frequent in SARS-CoV-2 infected patients 8 . We hypothesize that this might be related to the in ammatory status, as a consequence of the viral infection; alternatively, this could have been the result of a pre-existing condition that triggered the premature delivery and facilitated viral entry through the placenta.…”
Section: Discussionmentioning
confidence: 96%
“…Maternal physiological adaptations to pregnancy are known to increase the risk of developing severe illness in response to viral infections, such as in uenza; preliminary data suggest that the prognosis of SARS-CoV-2 infection could be more severe as well in pregnant women 8 . Vertical transmission of SARS-CoV and MERS, the two other animal coronaviruses known to infect humans, was never documented to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit still limited, there is evidence that SARS-Cov-2 can cause life-threatening situations also in pregnancy, even if fatal cases seem rare [5][6][7][8][9] . Severe pneumonia occurs in 5-16% of women 5,8,9 and may require prompt pregnancy termination for improving respiratory assistance. However, this evidence was drawn from case series, a study design that could overestimate the detrimental effects of SARS-Cov-2.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our reassuring clinical ndings are somehow in disagreement with recent evidence from large case series of affected pregnant women. Savasi et al reported on an Italian multicenter case series of 77 women hospitalized for Covid-19 and highlighted that one in ve delivered urgently for respiratory compromise or were admitted to an intensive care unit9 . Based on a retrospective case series in the USA, 7 out of 46 pregnant…”
mentioning
confidence: 99%